2020
DOI: 10.1016/j.cell.2020.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Structure of the Hippocampal Code for Space as a Function of Time, Context, and Value

Abstract: Highlights d Each CA1 pyramidal neuron has a propensity to have place fields that differs across cells d A cell's propensity is fixed across contexts and time, scaled in rewarded and novel areas d The subpopulation of low propensity cells yields a sparse code for location d Intracellular data provide evidence that excitability underlies propensity differences

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
143
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 87 publications
(182 reference statements)
15
143
1
1
Order By: Relevance
“…at the collection port) would provide a useful representation for learning about the target in the context of these foraging tasks. Moreover, unlike tasks that deliver reward at a variable target location(s) [71][72][73] , we did not find clear evidence for an enrichment of place fields nor enhanced decoding resolution 71 in the vicinity of the target location. dCA1 inactivation during foraging trajectories had no clear effect on performance (Fig.…”
contrasting
confidence: 95%
See 2 more Smart Citations
“…at the collection port) would provide a useful representation for learning about the target in the context of these foraging tasks. Moreover, unlike tasks that deliver reward at a variable target location(s) [71][72][73] , we did not find clear evidence for an enrichment of place fields nor enhanced decoding resolution 71 in the vicinity of the target location. dCA1 inactivation during foraging trajectories had no clear effect on performance (Fig.…”
contrasting
confidence: 95%
“…One of the most robust features that determines dCA1 activity is an animal's allocentric position in space 2 . The performance of a task, depending upon its demands, can enhance [71][72][73] or reduce 49,77 the relative contribution of spatial position to hippocampal and entorhinal activity 71 . In addition, population activity of dCA1 also represents non-navigational information, such as task events and elapsed intervals 10,14,44,45,78,79 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the proportion of reward coding neurons reported previously ( Gauthier and Tank, 2018 ), the number of cells recorded in our task and the percentage of stimulation responsive cells, we estimate that on average only one or two reward coding neurons may have been activated during our Reward-PC stimulations. In addition, recent experiments report an increased field density of neurons encoding conjunctively the reward and the location rather than a purely reward location-specific sub-population ( Lee et al., 2019 ). Future experiments will be required to fully dissociate these populations and assess their functional roles independently.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation of differences that we have observed in Arc expression across the CA1 longitudinal axis could be related to cellular excitability and intrinsic recruitment propensity. In dorsal CA1, several studies have reported that cellular recruitment does not follow a Poisson process (random draw with replacement), but instead is gamma or log-normally distributed [29, 30, 42]. Recently, Lee et al (2020) found that most cells in CA1 are virtually “silent” and have no place fields across multiple, large environments, while some cells have single fields, and a minority of cells have multiple fields in multiple environments – in keeping with recruitment statistics of hippocampal cells in multi-room IEG studies [42].…”
Section: Resultsmentioning
confidence: 99%